Local Anesthesia in Interventional Radiology - Li, Xin; Trerotola, Scott O. (Seminars in Interventional Radiology, 2022)
Interventional radiology is an evolving field that treats a variety of diseases. Local anesthetics is an important component of pain management during interventional radiologic procedures. It is highly effective and generally safe for routine procedures. However, local anesthetics can be associated with painful initial injection, allergic reactions, and rare but potentially devastating systemic toxicities. Recent evidence has shown that buffered solution and warm local anesthetics may reduce injection discomfort and improve clinical efficacy. Sensible safety practices and prompt recognition/treatment of the systemic toxicity are of paramount importance to provide safe local anesthesia. Interventional radiologists should be familiar with the basic pharmacology, common local anesthetics, optimizing strategies, complications, and management to provide safe and effective local anesthesia for patients.
Keywords: anesthesia; local anesthetics; pain control; medication; interventional radiology